PERAN APARATUR PENGAWAS INTERN PEMERINTAH DALAM REVIEW RENCANA KERJA ANGGARAN SEBAGAI QUALITY ASSURANCE KEBERHASILAN PENGANGGARAN KEUANGAN KABUPATEN BENGKULU UTARA - Ulfa, Dian Amalia; Fachruzzaman, Fachruzzaman; Abdullah, Abdullah (UNIB Press, 2020)
The purpose of this research is to know the role apparatus government internal control in review document work planning in the North Bengkulu Regency. The sample of this study was taken by census method. Data analysis in this research use descriptive statistic method. The results showed that: (1) the review or financial and program in the North Bengkulu Regency as good level. The dimension of reviews is planning, implementation and reporting. (2) the internal control system as supporting activity on reviews of financial and program, has a good level. The dimensions of supporting activities are internal control, risk appraisal, control activity, information and communication and controlling. Suggestion for Local Government of North Bengkulu Regency is to improve the realization of the role of effective internal government oversight apparatus, improve the risk assessment not maximal, especially on risk assessment in the workplace. Improving and able to establish and review on performance indicators and measures, maintaining and improving communication and information by utilizing various existing communication means and improving monitoring that has not been maximally monitored by conducting continuous monitoring.